2016
DOI: 10.2217/imt-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Blockade in Human Cancer Therapy: Lung Cancer and Hematologic Malignancies

Abstract: Tumor immune evasion is one of the hallmarks of cancer, and expression of the B7 family of immune checkpoints (PD-L1, PD-L2, B7-H3, B7x and HHLA2) is one mechanism of immune evasion by tumors to suppress T-cell function. Antibodies blocking these interactions of B7-1/B7-2/CTLA-4 and PD-L1/PD-L2/ PD-1 have had remarkable clinical success in several cancers and are less toxic than traditional chemotherapy. Even though only a small proportion of patients respond to checkpoint blockade, the duration of such respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Murine models have shown that blocking any of PD-1 [99,100], PD-L1 [100,101], or PD-L2 [101] has beneficial effects in inhibiting the growth and spread of tumors; conversely, constitutive expression of PD-L1 by tumor cells leads to enhanced resistance to CD8 + T cell-mediated cytolysis [102]. In a series of exciting developments, inhibitors of the PD-1 signaling pathway have shown considerable efficacy in numerous clinical trials involving patients with malignant disease who have failed conventional therapies (reviewed in [103,104]). Thus, in addition to understanding the effects of the PD-1 signaling pathway on fungal pathogenesis (reviewed below), it will be essential to ascertain whether the expanding clinical use of checkpoint inhibitors will alter the susceptibility or severity of fungal infections in patients treated with these immunotherapy agents.…”
Section: Immunoregulatory Signaling Pathwaysmentioning
confidence: 99%
“…Murine models have shown that blocking any of PD-1 [99,100], PD-L1 [100,101], or PD-L2 [101] has beneficial effects in inhibiting the growth and spread of tumors; conversely, constitutive expression of PD-L1 by tumor cells leads to enhanced resistance to CD8 + T cell-mediated cytolysis [102]. In a series of exciting developments, inhibitors of the PD-1 signaling pathway have shown considerable efficacy in numerous clinical trials involving patients with malignant disease who have failed conventional therapies (reviewed in [103,104]). Thus, in addition to understanding the effects of the PD-1 signaling pathway on fungal pathogenesis (reviewed below), it will be essential to ascertain whether the expanding clinical use of checkpoint inhibitors will alter the susceptibility or severity of fungal infections in patients treated with these immunotherapy agents.…”
Section: Immunoregulatory Signaling Pathwaysmentioning
confidence: 99%
“…Numerous studies have shown that blockade of the PD-1 signaling pathway can promote enhanced immune responses against cancers by altering important immunomodulatory mechanisms active in established tumor microenvironments (29–31, 43, 44). Having identified that PD-1 and its ligands were upregulated on immune effector cells in the lungs of mice with persistent cryptococcal lung infection, our next objective was to determine whether antibody-mediated blockade of this pathway could improve fungal clearance in this model.…”
Section: Resultsmentioning
confidence: 99%
“…Our interest in studying this pathway in the context of fungal persistence stems from studies demonstrating that PD-1 signaling impairs clearance of some viral (24–26) and bacterial pathogens (27, 28). Furthermore, numerous studies have shown that this pathway promotes tumor immune evasion which has led to the development of potent immune checkpoint inhibitors which effectively treat tumors in mice (29, 30) and humans (reviewed in (31, 32)).…”
Section: Introductionmentioning
confidence: 99%
“…They are recognized as inhibitory receptors on T cells and can regulate the activation and tolerance of T cells [11]. Several reports have shown that PD-L1 and PD-L2 have important but opposing roles in modulation of T-cell functions [24,25]. Usually, PD-1/PD-L1 interaction can stimulate the production of IL-4, producing a Th2 response and increasing lung inflammation and airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%